Methoxy substituted furan chalcones: an insight into anti-inflammatory, antioxidant, antidiabetic, antibacterial, and molecular docking studies - Ghorpade, Sujay A.; Kulkarni, Arati S.; Dandge, Padma B.; Chaugule, Hanmant N.; Ingle, Snehal S.; Bavi, Rohit S.; Bhosale, Raghunath B.; Peerzade, Nargisbano A.; Zaki, Magdi E. A.; Masand, Vijay H.; Patil, Nita R.; Jadhav, Shravan Y. (ChemistrySelect, 2026)
A series of methoxy-substituted furan-based chalcones (5a-m) were synthesized, characterized, and evaluated for in vitro anti-inflammatory, antioxidant, antidiabetic, and antibacterial activities. Among the series, compounds 5l, 5j, 5h, 5a, 5g, 5f, 5c, 5k, and 5e showed remarkable anti-inflammatory activity when compared to diclofenac sodium. The compounds 5k, 5e, 5m, 5h, and 5l showed outstanding activity in the DPPH free radical scavenging experiment, along with remarkable ferric ion reducing power activity in comparison to standard ascorbic acid. Compounds 5l, 5m, and 5g demonstrated significant alpha amylase inhibitory activity, comparable to that of the standard drug Acarbose, suggesting their potential as effective antidiabetic agents along with a good antibacterial profile against S. aureus and E. coli. The molecular docking studies revealed that compounds 5f and 5c showed the best docking profiles with BSA, while 5l and 5m demonstrated superior binding characteristics with amylase, highlighting their potential as promising bioactive candidates.
Keywords: Anti-inflammatory; Antibacterial; antidiabetic; Antioxidant; methoxy substituted furan chalcones; Molecular docking